EXPLORING CONNECTIONS BETWEEN ETHICAL CLIMATE AND ORGANIZATIONAL INNOVATIONS IN SERBIAN IT SECTOR - Šćepanović, Vesna; Šćepanović, Ivan; Žikić, Srđan; Stevanović, Mirjana (ACADEMIC REVIEW, 2024)
In the modern business environment, innovations represent an important component of organizational success. This paper explores the nature of the interrelationship between ethical practices and innovation. Companies that respect ethical norms often enjoy greater consumer trust, while unethical behavior can hinder creative processes, creating fear and mistrust among employees. In the research conducted for the purposes of this work, two standardized questionnaires were used: the Ethical Climate Questionnaire (ECQ) and the Keys to Creativity and Innovation Instrument (KEYS). The research was conducted in IT companies operating on the territory of the Republic of Serbia in the period from December 2023 to July 2024. This paper deals with the question of how ethical relations within the organization influence the innovative behavior of employees. The obtained results indicate that certain dimensions of the ethical climate can significantly influence the development of the innovative environment, that is, that a positive ethical climate in the organization has a stimulating effect on the components of the innovative/creative work environment.